Phytochemical mediated synthesis of ZnO:Dy3þ nanophosphors: JuddeOfelt analysis, structural and spectroscopic properties - Vasudevan, Prathibha (H. : ĐHQGHN, 2020)
In the present work, ZnO:Dy3þ nanophosphors were synthesized by a simple, cost effective and ecofriendly route using the aqueous extract of Azadirachta Indica leaves. The prepared ZnO:Dy3þ nanophosphors were characterized using X-ray diffraction (XRD), Fourier Transformed Infra-Red (FTIR), Raman, UV-VIS diffuse reflectance (UVDR) spectroscopy and Photoluminescence (PL), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray spectroscopy (EDX). TEM and X-ray diffraction analyses reveal the hexagonal wurtzite structure of the ZnO nanoparticles in the prepared samples. UV-VIS-NIR spectrum of the ZnO:Dy3þ nanophosphor was analysed on the basis of JuddeOfelt (J-O) theory and the JeO intensity parameters (Ul) were calculated. The radiative properties, such as radiative transition probability, branching ratio, stimulated emission crosssection and optical gain were investigated using the JeO intensity parameters. The photo luminescence emission spectra (PLE) of the Dy3þ doped samples exhibits three emission bands relative to 4F9/2/6H15/2 (478 nm), 4F9/2/ 6H13/2 (572 nm) and 4F9/2/ 6H11/2 (663 nm) transitions of Dy3þ ions respectively. The CIE chromaticity color coordinate shows that the ZnO:Dy3þ nanophosphors can be useful for white luminescence applications. The result indicates that the prepared phosphors produce white light emission and can be used for near ultraviolet excited white light emitting diode (NUV WLED) applications.